Local Government Understanding in Regional Development Planning: Systematic Literature Review - Mumtaza Azzahiroh; Salahudin Salahudin; Ali Roziqin (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to explore the understanding of the role of local government in regional development planning, which in this study uses the literature review method, namely by reviewing articles in previous studies so that they can provide an overview of how the role of local governments in regional development planning is, these data are obtained through the Scopus database and processed using the VOSviewer application. This research will focus on explaining how the role of local government in regional development planning. The role of local government in regional development planning is a government with a very strategic authority and position. This is related to its function as a public service provider to improve welfare, prosperity, and peace for the community. Regional development planning is an activity to be carried out in the future, in this case starting from several stages of the program preparation process and activities that involve various elements in it. This research shows that the role of local governments is to play an important role in planning housing development in an area, managing and coordinating the development of destinations in contemporary society, building an active role in institutionalizing urban resilience, developing the tourism sector in an area, and having an important role in planning to accelerate urban development. extracting integrated theories and methods for community development and planning at each location in an area.